Thin film surfaces suitable to multimodal ionization for TOF‐SIMS and LDI mass spectrometry of biomolecules. (2nd April 2014) - Kim, Shin Hye; Shon, Hyun Kyong; Lee, Tae Geol; Han, Sang Yun; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; Lee, Jae Cheol; Yi, Keewook; Hong, Tae Eun
<x xml:space="preserve">Abstract</x> We report that the flat surfaces of thin films (50‐nm‐thick Si and Au) prepared on thermal insulator (SiO2) substrates provide versatile sample plates exhibiting multimodality for TOF‐SIMS and LDI MS (laser desorption ionization mass spectrometry). Previously, the crystalline Si thin film was reported to be applicable to matrix‐free LDI of biomolecules using SOI (silicon‐on‐insulator) wafers. One of the benefits from the previous LDI method is that various surface materials can be employed while still maintaining LDI performance, including materials that are also amenable to TOF‐SIMS ionization. In this work, we demonstrate that SOI wafers (50‐nm‐thick Si on SiO2) and Au thin films (50‐nm‐thick Au on glass wafer) display sensitive ionization of peptide and drug molecules both in TOF‐SIMS and LDI MS, offering an important platform for multimodal ionization that will open a new opportunity combining unique advantages of each mass spectrometry for bimolecular detection. Copyright © 2014 John Wiley & Sons, Ltd.